GOVERNMENT PROCUREMENT OF GOODS AND SERVICES SERVICES AT THE GORONTALO CULTURAL HERITAGE PRESERVATION CENTER - Hadi Saputro Wirakusumah; Asna Aneta; Fenti Prihatini Dance Tui (Journal of Artificial Intelligence and Digital Economy, 2024)
The stages of implementing government goods and services procurement services are unclear and the factors determining success are not yet known in government agencies. This can lead to low public trust in the government procurement service process for goods and services. The aim of the research is to obtain an overview of the stages of implementation of government goods and services procurement services as well as the factors determining their success. This research was carried out at the Gorontalo Cultural Heritage Conservation Center. The research method used is descriptive qualitative with an inductive approach and analyzed in stages through data reduction, data presentation and drawing conclusions. The data sources for this research consist of primary and secondary data. Primary data is selected informants related to goods/services procurement activities and providers who have carried out work at the agency. Secondary data is supporting data in the form of printed documents and related files. Data collection was carried out by means of observation and in-depth interviews. The results of this research show that there are two stages in the procurement of goods and services that are not optimal. The two stages in question are the procurement preparation stage and provider selection. Apart from that, human resource competency and standard operational procedures as determining factors for service are still not optimal. It is hoped that with future improvements, outputs from the provision of goods and services procurement services can be achieved that are transparent, effective, efficient and fair, right on target and with minimal abuse of authority.